2020
DOI: 10.3846/btp.2020.11215
|View full text |Cite
|
Sign up to set email alerts
|

Dentification the Ways of Counteraction of the Threats to the Financial Security of High-Tech Enterprises

Abstract: Identified key external and internal threats significantly affect the process of ensuring the financial security of the enterprise. The application of the mechanism of counteraction to the influence of external and internal threats is characterized by important. The mechanism for countering threats to the financial security of a high-tech enterprise, unlike existing ones, combines a certain essence and hierarchical ordering of the influence of key external and internal threats, involves targeted tracking of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…Both foreign and domestic scholars like Stiglitz (2010), Lopez-Claros (2014), Benigno (2013), Krugman (2008), Roubini (2015), Vasyltsiv (2011), Helberg (2011 researched the issue of the formation of an anti−crisis policy in order to provide financial security at the macro and micro levels. Franchuk et al (2020) explored the main ways to counter financial security threats, but we focused more on the legal aspect and the state level. Sylkin et al (2019) demonstrated how crisis management can significantly contribute to ensuring financial security, when our study is more about identifying the main factors influencing its level and demonstrating the level of importance of the legal aspect on financial security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both foreign and domestic scholars like Stiglitz (2010), Lopez-Claros (2014), Benigno (2013), Krugman (2008), Roubini (2015), Vasyltsiv (2011), Helberg (2011 researched the issue of the formation of an anti−crisis policy in order to provide financial security at the macro and micro levels. Franchuk et al (2020) explored the main ways to counter financial security threats, but we focused more on the legal aspect and the state level. Sylkin et al (2019) demonstrated how crisis management can significantly contribute to ensuring financial security, when our study is more about identifying the main factors influencing its level and demonstrating the level of importance of the legal aspect on financial security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The issue of ensuring and assessing the safety of the enterprise today is one of the important objects of research by many scientists (Franchuk et al, 2020;O. Biliomistniy, I. Bilomistna, & Galushko, 2017;Burkaltseva et al, 2017;Britchenko et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientific works are devoted to the justification of modern methodological approaches to the assessment of the level and position of the financial security of an enterprise are: Azarenkova et al (2018), Britchenko et al (2018), Khudoliei (2018), Hryhoruk et al (2019), Kosaynova et al (2019), Drobyazko et al (2020), Franchuk et al (2020), Kharchuk et al (2020), Kondratenko et al (2020), Sylkin et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The main approaches to estimating the level of financial security of the enterprise, which are currently presented in the professional literature -are the coefficient, which involves the calculation of a set of financial indicators (Delas et al, 2015;Yeletskykh, 2017;Pera, 2017;Kharchuk et al, 2020); integrated, based on the definition of an integrated indicator of financial security (Ganushchak, 2017;Khudoliei, 2018;Azarenkova et al, 2018;Kosaynova et al, 2019;Kharchuk et al, 2020); based on the diagnosis of the probability of bankruptcy (Valaskova et al, 2020;Sylkin et al, 2018Sylkin et al, , 2019Sylkin et al, , 2020Koleda & Lāce, 2008;Bilomistniy et al, 2017;Britchenko et al, 2018;Nguyen & Nguyen, 2020;Franchuk et al, 2020). There are also several author's methods for assessing financial security: Hryhoruk et al (2019) -model for assessment of the financial security level of the enterprise based on the desirability scale; Zwolak (2017) -empirical model based on the Cobb-Douglas power function.…”
Section: Introductionmentioning
confidence: 99%